Aluno avaliado com baixo desempenho na perspectiva do professor do Ensino Fundamental II - Moraes, Nádia de Araujo Luciani Leite de (2019)
The present study addresses the student with learning difficulties, with low academic performance and analyzes the attitudes of teachers in the classroom to contribute positively to students school development. In addition, other questions that guided this research were: what criteria does the teacher use to identify the low-performance students? What is the teacher's responsibility when their students are unable to learn? This research was carried out in a private school in the countryside of São Paulo (Brazil), with Portuguese and Mathematics Middle School teachers. Semi-structured interviews were used to identify teachers' opinions about the low-performance students, the conduct of teachers in the classroom, the evaluation periods of the school and the meaning that the teacher attributes to the grade obtained. The collected data were analyzed based on Content Analysis, a procedure that allowed to construct five categories: Criteria to identify the student with low academic performance; Being a teacher and doing it on a daily basis; School: its resources, methods, and forms; The grade obtained is not a real indicator of school performance; and The extent of the learning process. For the discussion of the obtained data, the theoretical references werw preferably used Wallon, Ausubel and Luckesi. For teachers, students with learning difficulties present themselves in the classroom as being shy, ashamed, disorganized, discouraged, inattentive, among others. The school contributes with the teachers giving them autonomy so that they use different strategies for both activities and evaluations, in order to favor the students' learning. Some of the highlights are the importance of a close relationship and affection with students who present difficulties, and how the teacher acts in the classroom stimulating curiosity and the motivation to learn. For the teachers, the grade obtained in the test is not the only factor to measure the knowledge of the student